2016
DOI: 10.1016/j.bjorl.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

The role of the mean platelet volume and neutrophil-to-lymphocyte ratio in peritonsillar abscesses

Abstract: The mean platelet volume and neutrophil-to-lymphocyte ratio values made us think that these parameters were quick, inexpensive and reliable inflammatory follow-up parameters and could be easily integrated into daily practice for peritonsillar abscess treatment except platelet count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
2
19
2
1
Order By: Relevance
“…Patients with acute community-acquired pneumonia had lower MPV values than healthy control group (36). In patients who were followed up with peritonsillar abscess diagnosis, MPV values before treatment were found to be higher than those after treatment and control group (37). In studies evaluating platelet parameters in acute infections, quite different results have been obtained.…”
Section: Discussionmentioning
confidence: 94%
“…Patients with acute community-acquired pneumonia had lower MPV values than healthy control group (36). In patients who were followed up with peritonsillar abscess diagnosis, MPV values before treatment were found to be higher than those after treatment and control group (37). In studies evaluating platelet parameters in acute infections, quite different results have been obtained.…”
Section: Discussionmentioning
confidence: 94%
“…A recent PubMed search using the key word "NLO" revealed 339 papers published in the year 2016. Searching for papers about ENT excluding malignancies, we found that elevated NLO has been investigated in facial paralysis, nasal polyp, cholesteatoma, and peritonsillar abscess [1][2][3][4][5][6]. The above-mentioned studies have compared NLO between nasal polyp patients and a healthy control group and determined high NLO in the nasal polyp patients; however, they found no difference in terms of TLO [2].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of studies on NLO and TLO has been increasing in recent years. A PubMed search revealed 339 papers written on NLO [1][2][3][4]. NLO and TLO have been designated as inflammatory markers that can be routinely studied in the peripheral blood without additional cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akut toplum kaynaklı pnomonisi olan hastalarda sağlıklı kontrol grubuna göre daha düşük OTH de- ğerleri saptanmıştır (36). Peritonsiller apse tanısı ile izlemi yapılan hastalarda tedavi öncesi OTH değerleri, tedavi sonrası ve kontrol grubuna göre daha yüksek olarak bulunmuştur (37). Akut enfeksiyonlarda trombosit parametrelerinin değerlendirildiği çalışmalarda oldukça farklı sonuçlar elde edilmiştir.…”
Section: Boswbc (Mm³)unclassified